Overview Of Family Informative And Emotional Support About FE Supplementation To Anemia In Adolescent Girls At Stikes Rajekwesi Bojonegoro - Azizah, Nur; Muhidayati, Wiwik; Arsita Sari, Suci; Lestari, Puji; Pinandia Sustamy, Raffiky (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Background: Adolescent girls are one group that is prone to suffering from anemia, This is because young women lose iron (Fe) during menstruation so they need more iron (Fe) intake. TTD is given to rheumatism and WUS through supplementation containing at least 60 mg of elemental iron and 400 mcg of folic acid. Objective research is to discribe the informational dan emotional family support to fe suplementation Method: This research uses descriptive research where researchers search description of the object under study. the number of samples was 45 respondents Adolecent girls in High school of science Rajekwesi Bojonegoro, Data collection used a questionnaire instrument and displayed in percentages Result: Research is known that of the 45 respondents, the majority of respondents, namely 22 (48.89%) did not receive enough family informative support is known that of the 45 respondents, the majority of respondents, namely 20 (44.43%) did receive enough family emotional support. Conclusion : Most families provide insufficient informational support to adolescents regarding Fe supplementation in preventing anemia in adolescents, whereas Most families provide sufficient emotional support for Fe supplementation in adolescents at Rajekwesi Bojonegoro High School of Science